Weeds. Season six [videorecording (DVD)] - Ellis, Scott; Parker, Mary-Louise; Nealon, Kevin, 1953-; Kirk, Justin; Parrish, Hunter, 1987-; Gould, Alexander, 1994-; Kohan, Jenji, 1969- (Lionsgate, 2011)
Season 6 of this highly acclaimed series turns over a new leaf when pot-selling soccer mom Nancy Botwin tries to leave behind her illegal operations. Includes the complete Season 6 with all 13 episodes.